Identification of beagle food taking patterns and protocol for food effects evaluation on bioavailability - Guoqing Zhang (Nature Portfolio, 2018)
Abstract Food is a known primary role to the exposure of the drugs orally administered. Since each animal may have unique food taking pattern and it is difficult to manipulate the food taking to animals, there lacks rationalized protocol for the food effects in pre-clinic study. The objective of this study was to identify the beagle food taking patterns and demonstrate their effects on bioavailability in valsartan. Herein, four types of food taking patterns of beagle were identified via inter-day and intra-day analysis, and named as Persisting, Pulsing, Postponing, Pushing (“4P Modes”), respectively, which were also validated by principal component analysis (PCA). Interestingly, food intake resulted in a reduced area under the concentration-time curve (AUC0–12h), maximum concentration (Cmax) and absorption rate, whilst the reduction varied in “4P Modes” of food taking. General considerations in the design of experiment for food effect to the bioavailability in beagles have been established as: to recognize the food taking patterns in each animal, to confirm the inter-day stability of the food taking behaviors, to trace the food taking patterns in parallel with plasma sampling. In conclusion, the right animals with proper food taking patterns should be assessed and selected for pre-clinic bioavailability evaluations.